Sharia-Based Tourism Management in Improving Community Income in Teluk Bakau Village, Riau Islands Province - Helianto, Helianto; Mukhaer Pakkanna; Mochammad Yana Aditya; Gusti Oka Widana; Amie Amelia (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2025)
This study aims to analyze the management of sharia-based tourism in Teluk Bakau Village and its impact on increasing the income of the local community. Sharia-based tourism is one of the tourism development models that prioritizes Islamic principles in the service and management of tourist destinations. Thus, this study seeks to understand the extent to which the implementation of sharia tourism can contribute to the economic welfare of the surrounding community. This study uses a qualitative approach with a phenomenological method. Data were collected through interviews with tourists and business actors operating around the tourist area. Data analysis was carried out using the data reduction method to see the relationship between sharia-based tourism variables and community income. The results of the study indicate that the management of sharia-based tourism in Teluk Bakau Village has been implemented in several aspects, such as the provision of facilities in accordance with sharia principles and community involvement in tourism economic activities. However, there are obstacles in development, especially related to promotion and supporting infrastructure. The implications of this study emphasize the importance of government support and cooperation between business actors and the community in developing sustainable sharia tourism that has a positive impact on the local economy.